Kundur Island Resort Park Dengan Pendekatan Arsitektur Tepian Air - Suci Rahmadani; Wahyu Hidayat; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Kundur Island Resort Park is a resort area design that is equipped with recreation facilities located in Lubuk Beach, Tanjung Batu Kundur, Karimun Regency, Kepulauan Riau. LubukBeach is on an island surrounded by the sea which borders directly with neighboring Malaysia and Singapore. Lubuk Beach has beautiful scenery which is dominated by white sand and big rocks, so that it attracts the attention of foreign and domestic tourists. Theincreasing number of visitors to these attractions is the background of the need for resorts as lodging places for tourists who come far from outside the area. This design uses the theme ofWaterfront Architecture, which is the science of building design which is located on the border between land and water, which has main elements namely economic, social, tourism,and environment which are closely related to physical and visual factors of the area and can also change the image of water aesthetic support. Waterfront Architecture has 4 supportingelements which are the basis for the design of the Kundur Island Resort Park area, including Open Space, Connection, Development, and Sustainable. Concept used in this design isWater. Water is the primary need of living things as well as recreation . Water has a flexible and dynamic nature so that the design results in dynamic and flexible formations.keywords : Lubuk Beach, Tanjung Batu Kundur, Resort, Waterfront Architecture